CHANGE OF THE FUNCTION OF GREEN OPEN SPACE (RTH) LAND INTO COMMERCIAL LAND IN GAMPONG TIBANG, SYIAH KUALA DISTRICT: According To The Concept Of Maslahah - Nurjannah, Raihan; Yahya, Faisal; Akbar, Hajarul (Al-Iqtishadiah: Jurnal Hukum Ekonomi Syariah, 2024)
This research aims to examine the change in the function of green open space (RTH) into commercial land in Gampong Tibang, Syiah Kuala District, Banda Aceh, based on the concept of maslahah. Changes in land function in Gampong Tibang include the conversion of RTH land into residential areas, businesses, and public facilities that conflict with the ecological function of the land. This phenomenon has a significant impact, such as decreasing environmental quality, decreasing water absorption capacity, and increasing the risk of flooding. This study uses an empirical legal approach with a descriptive qualitative analysis method. Data were obtained through interviews, observations, documentation, and literature studies. The results of the study show that there has been a change in the function of RTH in Gampong Tibang due to rapid urbanization which has encouraged the conversion of RTH in Gampong Tibang into residential and commercial areas. Although in accordance with Banda Aceh City Qanun Number 2 of 2018 and Perwal Number 13 of 2021 concerning RDTR, this change reduces water absorption capacity and increases the risk of tidal flooding. Land conversion is strictly regulated through the RTRW and RDTR, which allow changes according to their designation. However, ecological impacts and sustainability must be considered so that development continues to support environmental balance. From a maslahah perspective, this change fulfills the basic needs of society (maslahah dharuriyyah) such as housing, but still requires careful planning to ensure environmental sustainability and the long-term welfare of future generations